Butuh Dukungan Bukan Teror saat Berjuang dalam Pemulihan dari COVID-19 - Silalahi, Malianti (Journal of Telenursing (JOTING), 2023)
This research aims to explore in depth the experiences of COVID-19 patients in motivating themselves to recover. This research method uses a phenomenological study approach with in-depth interviews, sampling techniques using purposive sampling, and analysis using the Colaizzi stage. The results of the research show that there are four themes, namely hiding a positive status for COVID-19 as a coping mechanism that is considered the safest for achieving self-healing, the experience of helplessness is a driving factor for recovery, a support system that is not excessive provides enthusiasm to rise and recover from COVID-19, The support system forms positive affirmations to get up and undergo treatment. In conclusion, there are four themes that participants perceive when struggling to recover from COVID-19. It is essential to provide support to COVID-19 patients so that they can recover optimally, but not excessive reliance that could be considered terror. Keywords: COVID-19, Helplessness, Coping Mechanisms, Motivation, Support System